RESPONS PERTUMBUHAN DAN PRODUKSI CABAI MERAH (Capsicum annuum L.) VARIETAS AKAR DAN LOTANBAR TERHADAP DOSIS PUPUK NPK - Galang Fairroman Sanda; Yohannes Cahya Ginting; Hidayat Pujisiswanto; Nyimas Sa’diyah; Husna Fii Karisma Jannah; Ryano Ramires; Qudus Sabha Adhinugraha; Rani Yosilia (JURNAL AGROTROPIKA, 2026)
Red chili (Capsicum annum L.) is one of important horticultural crop and a leading commodity among 18 types of commercial vegetables cultivated in Indonesia. Red chili productivity is influenced by soil fertility, while chili plants in Lampung are generally planted on ultisol soil. Ultisol soil is a type of soil that is poor in the nutrients N, P, and K, and has soil acidity problems. One form of effort to improve ultisol soil is by applying fertilizer. This research aims to determine the response of growth and production of Akar and Lotanbar varieties of red chilies to the dose of NPK fertilizer applied, so that we can find out the dose of NPK fertilizer that can increase the growth and production of red chili plants. This research used a Randomized Block Design which was prepared factorial 2 x 4 with 3 repetitions. The data obtained were tested for homogeneity of variance using the Barlett test and the additivity of the data was tested using the Tukey test. If these two results meet the assumptions, the data is analyzed using analysis of variance, separating the middle value and then testing the middle value using the 5% BNT test. The research results show that the NPK fertilizer dose of 30 g/plant is the best dose that can increase the growth and production of red chili plants varieties Lotanbar and Akar, in general the response of chili plants to doses of NPK fertilizer is not influenced by plant variety or vice versa.Keywords : Red chili, ultisol, fertilizer, NPK, dose